Velocity Field Analysis of Bonding Interface on Cold-Rolled Copper/Aluminum Composite Plate. Issue 7 (July 2017) - Qingxue, Huang; Jiang, Zhang; Lin, Zhu; Li, Jiang; Xiangyu, Gao
Abstract: The cold-rolled bonding process of copper/aluminum bimetal plate was investigated by the velocity field of finite element method (FEM). At the same time, deformation characteristics of metal were analyzed in the bonding process. The study method was to combine theory calculation with field data. The circumferential velocity of rollers, rolling reduction rate, synchronous rolling of non-equal sized rollers and asymmetrical rolling of non-equal sized rollers were analyzed. Results show that the velocity field can explain the cold-rolled bonding process of copper/aluminum bimetal plate more effectively; the synchronicity of metal flow on bonding surface decreases with the increase of circumferential velocity about rollers near the exit of deformation area, and the bonding strength is reduced; in the process of synchronous rolling about non-equal sized rollers, diameter ratio of the rolls is 1.4∼1.6 with a great synchronicity of metal flow near the exit of deformation area and a high bonding strength; in the process of asymmetrical rolling about non-equal sized rollers, the circumferential velocity rate of rollers is 1.2 with a great synchronicity of metal flow near the exit of deformation area and a high bonding strength.